Chemical partitioning and antioxidant capacity of green coffee (Coffea arabica and Coffea canephora) of different geographical origin. (March 2016) - Babova, Oxana; Occhipinti, Andrea; Maffei, Massimo E.
Graphical abstract: Green coffee bean extracted from Coffea arabica and C. canephora of different geographical origin show a clear chemical pattern that corresponds to the antioxidant capacity. Highlights: Chlorogenic acids and caffeine allow partition of green coffee for geographical origin. The antioxidant capacity of green coffee is correlated to the chlorogenic acids content. Coffea canephora contains higher caffeine than C. arabica. Coffea arabica from Kenya has the highest chlorogenic acids/caffeine ratio. Abstract: Green coffee beans of Coffea arabica and Coffea canephora accessions from different geographical origin (Brazil, Colombia, Ethiopia, Honduras, Kenya, Mexico, Peru, Uganda and Vietnam) were extracted and the extracts analyzed by HPLC–ESI-MS/MS for the identification and quantification of chlorogenic acids and caffeine content. Principal component and cluster analyses were used to identify chemical patterns separating the different species and accessions based on their geographical origin. C. canephora showed always a higher caffeine content with respect to C. arabica, whereas the C. arabica accessions from Kenya showed a higher chlorogenic acids and a lower caffeine content. The antioxidant capacity of green coffee extracts was assayed by the reducing power and DPPH assays. The antioxidant capacity correlated with the chlorogenic acids content. The results show that the C. arabica from Kenya possesses the highest chlorogenic acids/caffeine ratio and, among the C. arabica accessions, the highest antioxidant capacity. Therefore, the C. arabica from Kenya is the most suitable green coffee source for nutraceutical applications because of its high antioxidant capacity and low caffeine content.